On his Birth Centenary - Satija, M.P. (DESIDOC Journal of Library & Information Technology, 2002)
Brings out a life sketch of Dr Ranganathn as a legend. Gives an account of the achievements and milestones, he set during his life span and how the current status of libraries and the profession differs from that of his dreams. Highlights the national and international recognition of his work, and the awards and laurels conferred to him. http://dx.doi.org/10.14429/dbit.12.5.3066